LATE CARBONIFEROUS PLUTONISM WITHIN THE PRE-ALPINE BASEMENT OF THE EXTERNAL HELLENIDES (KITHIRA, GREECE): EVIDENCE FROM U-PB ZIRCON DATING - Xypolias P.; Dörr W.; Zulauf G. (My University, 2006)
U - Pb zircon dating of three granitic orthogneisses, sampled from Kithira island, SW Greece, provide the first reliable evidence for Carboniferous plutonism within the pre-Alpine basement of the External Hellenides. Concordant zircons from two samples yielded ages at 324 ± 2 Ma and 323 ±3 Ma, whereas the third sample yielded a lower intercept age at 320 ± 1.2 Ma. The concordant ages are interpreted to date the emplacement of the igneous protolith. Ages of inherited zircons of two orthogneisses range from 2.5 to 2.4 Ga, indicating Late Archaean-Early Proterozoic crustal components. In combination with published ages for other Aegean metagranitoids, the new U-Pb ages provide additional evidence of a temporally restricted period of plutonism in the pre-Alpine Aegean region from 325 to 300 Ma. Comparing the post-Neoproterozoic evolution of the investigated basement with that of the Cycladic and Pelagonian basements and of the continental massifs of NE Greece and Turkey, we argue that all these crustal blocks were part of the Gondwana-derived Cimmerian terrane. Based on the spatial and temporal distribution of Late Carboniferous Aegean plutonism, we suggest that this period of magmatic events results from the southward subduction of Palaeotethys beneath the marginal fragments of northern Gondwana.
Keywords: Carboniferous; Neoproterozoic; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская